上顎歯肉に発生した周辺性エナメル上皮癌の１例 - 下岡, 拓矢; 趙, 正秀; 和田, 剛信; 藤原, 采香; 田中, 晋; 松岡, 裕大 (日本口腔外科学会雑誌, 2025)
Peripheral ameloblastic carcinoma is an extremely rare malignant odontogenic tumor arising outside the jawbone. We report a case of peripheral ameloblastic carcinoma in the maxilla. The patient was an 81-year-old woman. A neoplastic lesion on the left maxillary gingiva was noted by a local dentist and she was referred to the department of oral surgery of a hospital. A biopsy was performed, however it was difficult to determine whether it was benign or malignant, therefore the patient was referred to our hospital for further examination and treatment. A contrast-enhanced CT image of the maxillofacial region revealed only mild compressive bone resorption in the buccal cortical bone on the left side of the maxilla. Clinically, however, the surface of the tumor was rough and prone to bleeding. Cytopathology resulted in possible signs of malignancy. An excisional biopsy revealed a high degree of cellular atypia, and a preoperative diagnosis of ameloblastic carcinoma was made. A partial maxillectomy was performed under general anesthesia. Based on the histological findings of the resection specimen, a diagnosis of ameloblastic carcinoma was made. One year and ten months have passed since the surgery, and there has been no evidence of recurrence or metastasis.